2009
DOI: 10.1021/jp9058406
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Stability of Gold Nanoflowers by the Seeding Approach: The Effect of Intraparticle Ripening

Abstract: The seeding approach for preparation of gold nanoflowers in which 25 nm gold nanoparticles were used as the seeds and a mixture of HAuCl4 and hydroxylamine as growth solution was investigated systematically. It is revealed that the formation and stability of the nanoflowers were affected greatly by the intraparticle ripening induced by the chlorine ions that existed in the reaction system. In this seeding approach, hydroxylamine promoted the rapid reduction of HAuCl4 and thus rapid formation of small Au partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
117
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(122 citation statements)
references
References 42 publications
3
117
2
Order By: Relevance
“…Small s-GNPs (SPR band at 518 nm corresponding to a mean diameter of approximately 11 nm) were used as the seeds and a mixture of HAuCl4, sodium citrate and hydroquinone as the growth solution. It is somewhat unclear if the growth of the branch is dominated by the epitaxial mechanism or by the random attachment of the small GNPs on the seeds surface [22], however, the hypothesis is the occurring stepwise reduction of Au III to Au I by citrate and Au I to Au 0 by hydroquinone [21].…”
Section: Preparation Of Dr-gnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Small s-GNPs (SPR band at 518 nm corresponding to a mean diameter of approximately 11 nm) were used as the seeds and a mixture of HAuCl4, sodium citrate and hydroquinone as the growth solution. It is somewhat unclear if the growth of the branch is dominated by the epitaxial mechanism or by the random attachment of the small GNPs on the seeds surface [22], however, the hypothesis is the occurring stepwise reduction of Au III to Au I by citrate and Au I to Au 0 by hydroquinone [21].…”
Section: Preparation Of Dr-gnpsmentioning
confidence: 99%
“…Although QDs are particularly suited for multiplexing because of the tunable color of the emitted fluorescence, still they require a light source for excitation, thus limiting the portability and cost-effectiveness of QD-based ICSTs. Metal nanoparticles also offer the opportunity of tailoring the SPR band (and thus the color) by varying NP dimension and shape [21][22]. In fact, the advantage of using differently shaped and therefore differently colored silver nanoparticles as labels for multiplex ICST has been demonstrated by Yen et al [23].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, using a seed-mediated growth process, Yuan and his coworkers 8 synthesized multi-branched urchin-like gold nanoparticles in the AgNO 3 -ammoniacal solution. Yang 17 and his coworkers prepared gold nanoflowers by using 25 nm gold nanoparticles as the seeds and a mixture of HAuCl 4 and hydroxylamine as growth solution. But their application is restricted because of tedious work involved in the preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Ni et al reported flowerlike ZnOZnS heterogeneous microstructures built up by ZnSparticle-strewn on ZnO microrods by a hydrothermal route [8]. Some other flowerlike and hierarchical micro/ nanostructures (including metal or ternary compounds) were also reported, such as Au [9] [27][28][29], electrochemical deposition [30][31]. Among them, the solution approach has been proved to be an efficient way with outstanding advantages, such as simplicity, commercial feasibility and potential for scaling up.…”
mentioning
confidence: 99%
“…Ni et al reported flowerlike ZnOZnS heterogeneous microstructures built up by ZnSparticle-strewn on ZnO microrods by a hydrothermal route [8]. Some other flowerlike and hierarchical micro/ nanostructures (including metal or ternary compounds) were also reported, such as Au [9], Bi 2 SiO 5 [10], Bi 2 S 3 [11], ZnS [12], InP [13], SnO 2 [14] and ZnS-ZnO heterostructures [15].…”
mentioning
confidence: 99%